2013
DOI: 10.1111/tbed.12160
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofToxoplasma gondiiin the milk of naturally infected goats in the Northeast of Brazil

Abstract: The aim of the present study was to detect the genomic DNA of Toxoplasma gondii in milk samples from naturally infected goats in the state of Pernambuco, (Brazil). In total, 248 blood serum samples were collected and processed from lactating goats and then submitted to a search for antibodies to T. gondii through the indirect immunofluorescence reaction. Samples with a score of 64 or more were considered positive. In total, 248 milk samples were collected and processed from the same group of goats in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
5
31
1
2
Order By: Relevance
“…The PCR results in the present study are much higher than recently reported in Poland (3%) by Cisak et al (2017). A lower percentage (6%) was obtained in Brazil (Bezerra et al 2015) and Italy (13%) (Mancianti et al 2013). A relatively high prevalence (33%) was recorded by Spišák et al (2010) in Slovakia.…”
Section: Discussioncontrasting
confidence: 67%
“…The PCR results in the present study are much higher than recently reported in Poland (3%) by Cisak et al (2017). A lower percentage (6%) was obtained in Brazil (Bezerra et al 2015) and Italy (13%) (Mancianti et al 2013). A relatively high prevalence (33%) was recorded by Spišák et al (2010) in Slovakia.…”
Section: Discussioncontrasting
confidence: 67%
“…Transmission by food may occur with the ingestion of sporulated oocysts present in vegetables or water and/or tissue cysts present in raw or undercooked meat. The transmission of T. gondii with raw milk has been reported and several studies demonstrated the presence of the parasite’s DNA in sheep milk (Bezerra et al , 2015; de Santana Rocha et al , 2015; Luptakova et al , 2015). In Italy, the consumption of sheep milk (397.510 ton in 2015) is second only to the consumption of cow milk (11.161.224 ton in 2015) (www.istat.it).…”
Section: Introductionmentioning
confidence: 99%
“…In the light of the importance of products of goat origin as a human food source, contamination of such products by the protozoon Toxoplasma gondii when they are inadequately prepared can lead to public health problems in the form of toxoplasmosis. This infection is often neglected in developing countries, thus resulting in reproductive and economic losses among herds, particularly in rural and semi-rural areas (CAVALCANTE et al, 2008;BEZERRA et al, 2013). This is the second study to investigate toxoplasmosis among goats in the state of Rio Grande do Norte.…”
Section: Discussionmentioning
confidence: 99%
“…Goats' ability to eliminate T. gondii through their milk and the persistence of tissue cysts in goats (DUBEY, 1980) demonstrate the significance of this species in transmitting toxoplasmosis to humans (SACKS et al, 1982). Thus, when improperly prepared, the infected meat and milk of these animals is one of the most important potential sources of human toxoplasmosis (TENTER et al, 2000;CLEMENTINO et al, 2009;SANTOS et al, 2012;BEZERRA et al, 2013). Considering the high number of goat herds in northeastern Brazil and the economic losses caused by this parasite, the aims of this study were to investigate the seroprevalence of T. gondii among goats, along with the associated risk factors, and to identify recent and/or chronic infection by T. gondii in the Sertão do Cabugi region, Rio Grande do Norte, Brazil.…”
Section: Introductionmentioning
confidence: 99%